La prise en compte des élèves à « besoins éducatifs particuliers » au prisme des récits de pratiques enseignantes : les logiques en jeu en contexte d’école inclusive - Nicole Galasso-Chaudet; Bertrand Bergier (Recherches en Éducation)
This article is interested, first of all, in the changes arisen in France, since the construction of the school of Jules Ferry (1882) in our days, when it is about the consideration of the pupils at "Particular Educational Needs". Runner of a chronological and semantic exploration of the texts of law and the history of the name of the different pupils, we highlight three big periods which determine three types of school: "the segregationist school", "the integrative school" and "the including school". These three phases of evolutions take sense(direction) in the registers of justifications which allow to place the evolutions and the changes in the terms that the sociologists, Boltanski and Thévenot (1987) used to describe more general social models of skill(competence): the "civic world", the "domestic world" and the "industrial world" still called “model” or “logical” (Derouet, on 1988). In the current context of "the including school", we wanted "to meet" the teachers of ordinary class concerning the consideration of the pupils at "Particular Educational Needs". The methodology of the narratives of practices (Bertaux, on 1976) allows us to collect what the teachers of the first degree say of their practices, in the small facts of the everyday professional life. We show then, in reference to the various “worlds” (Boltanski and Thévenot, on 1991) and from the analysis of these narratives, how the logics of action (Boltanski and Thévenot, on 1991) show themselves and according to which composite assemblies (Derouet, on 1988) in the heart of the teaching practices. So, by studying the commitment (Galasso-Chaudet, 2013) teachers in the situations of inclusion, the led research brings tools for a better understanding of the work of primary school teachers.